An Empirical Study on the Influence of Product Quality, Price, and Corporate Image on Customer Satisfaction Towards Steel Mesh Fence Entrepreneurs in Thailand - Patjareesakul, Sarawut; Chaipoopirutana, Sirion (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
Abstract This study examines the factors influencing customer satisfaction with steel mesh fencing products, focusing on product quality, price, and corporate image. Using a descriptive and inferential research design, data were collected from 506 respondents across Thailand and analyzed using multiple linear regression. The findings reveal that product quality and corporate image significantly affect customer satisfaction, while price shows no substantial impact. Product quality, particularly dimensions like performance and reliability, and a strong corporate image, enhance satisfaction by fostering trust and credibility. Recommendations emphasize improving product reliability, leveraging brand positioning, and maintaining transparent communication. Future research should explore additional variables and customer segments to refine strategies for sustained satisfaction and long-term success in the steel mesh fencing industry.